CO2 insertion into epoxides using cesium salts as catalysts at ambient pressure. Issue 15 (8th July 2019) - Suleman, Suleman; Younus, Hussein A.; Ahmad, Nazir; Khattak, Zafar A. K.; Ullah, Habib; Chaemchuen, Somboon; Verpoort, Francis
Abstract : Cesium salts (Cs2 CO3, CsCl, and CsNO3 ) were used for the coupling of CO2 and epoxides. Abstract : Cesium salts (Cs2 CO3, CsCl, and CsNO3 ) were used for the coupling of CO2 and epoxides. These salts are highly active catalysts for the formation of cyclic carbonates from epoxides and CO2 at ambient pressure (1 bar). The reaction proceeds with high conversions up to 100% and turnover numbers (TONs) up to 97 × 10 3 .